2023
DOI: 10.3389/fimmu.2023.1178445
|View full text |Cite
|
Sign up to set email alerts
|

Differentially activated B cells develop regulatory phenotype and show varying immunosuppressive features: a comparative study

Elina A. Zheremyan,
Alina S. Ustiugova,
Aksinya N. Uvarova
et al.

Abstract: Regulatory B lymphocytes (Bregs) are B cells with well-pronounced immunosuppressive properties, allowing them to suppress the activity of effector cells. A broad repertoire of immunosuppressive mechanisms makes Bregs an attractive tool for adoptive cell therapy for diseases associated with excessive activation of immune reactions. Such therapy implies Breg extraction from the patient’s peripheral blood, ex vivo activation and expansion, and further infusion into the patient. At the same time, the utility of Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Over the past few decades, therapies specifically targeting B cells have proven highly effective in the clinical realm, particularly in the management of autoimmune diseases [ 120 , 121 ]. At the same time, the diverse range of immunosuppressive mechanisms exhibited by Bregs has positioned the adoptive transfer of these regulatory B cells as a promising therapeutic strategy for conditions marked by the overactivation of immune responses [ 78 , 122 ]. Looking forward, the potential of Breg cell therapy emerges as a beacon of hope for the treatment of cutaneous wounds, including the formidable challenge of chronic wounds resistant to current approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few decades, therapies specifically targeting B cells have proven highly effective in the clinical realm, particularly in the management of autoimmune diseases [ 120 , 121 ]. At the same time, the diverse range of immunosuppressive mechanisms exhibited by Bregs has positioned the adoptive transfer of these regulatory B cells as a promising therapeutic strategy for conditions marked by the overactivation of immune responses [ 78 , 122 ]. Looking forward, the potential of Breg cell therapy emerges as a beacon of hope for the treatment of cutaneous wounds, including the formidable challenge of chronic wounds resistant to current approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, NK-mediated inflammatory processes may hinder wound healing, especially in chronic wounds. In the immunosuppressive tumor setting, Bregs have been reported to suppress IFNγ production by NK cells via the production of IL10 [ 76 ] and to abrogate NK cell-mediated cytotoxicity [ 77 , 78 ]. Transcriptome analysis suggests that Bregs may produce several proteins with suppressive effects on NK cell activating receptors and effector mechanisms [ 27 ].…”
Section: Bregs Promote Cutaneous Wound Healing Via Several Mechanisms...mentioning
confidence: 99%
“…Different subsets of the same immune cells have different functions, such as T cells, which have the potential to differentiate into CD4+ T cells and CD8+ T cells, and CD4+ T cells can further differentiate into Th1, Th2, Th17, Treg, and other T-helper cell subsets. The mainstream view is that Th2 and Th17 are associated with an increased risk of AAD, while Treg has immunosuppressive effects; in addition, it has been found that the same immune cell subpopulations but different immune phenotypes have inconsistent roles in disease ( 6 ). As research on immune cells continues to deepen, the functional heterogeneity among subsets of the same immune cells has gradually been discovered by researchers; in order to achieve better therapeutic outcomes, people have begun to explore the changes in the roles of immune cells with different immunophenotypes.…”
Section: Introductionmentioning
confidence: 99%